ELECTROFLOTATION EXTRACTION OF POWDERED CARBON-BASED MATERIALS FROM AQUEOUS SOLUTION WITH USING OF SURFACTANTS - Kolesnikov Artem Vladimirovich; Milyutina Alyona Dmitrievna; Kolesnikov Vladimir Aleksandrovich; Zhurinov Murat; Baeshov Abduali; Yaskevich Vladimir Ivanovich (Academic Scientific Journal of Chemistry, 2019)
Comparative electroflotation studies of powdered carbon materials from an aqueous solution of sodium sulfate electrolyte were carried out. Kinetic electroflotation dependences of various carbon materials particles (carbon nanoflakes and activated carbons OU-B and BAU-A) are shown. It is established that the particles of carbon nanoflakes are most effectively extracted in the presence of nonionic surfactants. Whereas the extraction degree of activated carbons does not reach 20% in the same conditions. Electroflotation studies of powdered carbon materials from aqueous solutions with the addition of coagulants Al3+ and Fe3+ were carried out to improve the efficiency and intensity of particles extraction. We studied aqueous solutions containing different types of surfactants: anionic, cationic and nonionic. Studies have shown that carbon nanoflakes are extracted quite effectively regardless of nature either the coagulants or the surfactants. The extraction degree of activated carbon particles OU-B reached 90-95% if iron ions were present in an aqueous solution of cationic or nonionic surfactant. But the efficiency of the process was reduced in the presence of Al3+ due to the formation of a large amount of insoluble aluminum hydroxide. We also studied the surface characteristics of powdered carbon materials (electrokinetic potential (ζ-potential) and hydrodynamic radius of the particles) for a better understanding of the electroflotation process.